Pelatihan Pembuatan Paving Block menggunakan Limbah Plastik di Desa Sanrobone Kecamatan Sanrobone Kabupaten Takalar - Suriati Abd. Muin; Bulgis; Sattar Yunus (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
Sanrobone Village is a village with numerous residential settlements, leading to the production of household waste on a daily basis. To minimize plastic waste, training is essential to educate the residents about the utilization of plastic waste in the production of paving blocks. The goal of this community partnership program is to enhance the creativity of Sanrobone Village residents. Moreover, producing paving blocks from plastic waste not only contributes to environmental cleanliness but also boosts the economic activities in the village. The implementation method involves socialization, training in paving block production, and evaluation to assess the understanding, response, and success of the program. The training results indicate an improvement in understanding the process, with 88.89% of participants comprehending the production and benefits, while 11.11% understand the process but do not elaborate on the obtained benefits.